PENGARUH PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR IPA - Ema Maria Nirma (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
This research is aimed to describe the preferences of learning results in science using Number Head Together (NHT) model of cooperative learning method and conventional method towards 7thgrade students of SMP Taman Dewasa Jetis Yogyakarta. comparatively, this research his aimed to describe the difference of learning results in science using Number Head Together (NHT)Â  model of cooperative learning method with conventional learning method of 7thgrade students of SMP Taman Dewasa Jetis Yogyakarta academic year 2015/2016. This research is a Quasi-Experiment. The researcher used random sampling as the technique of collecting the sample. Descriptively, the research results showed that the learning results in the science of the class given number head together with the model in cooperative learning method in SMP Taman Dewasa Jetis Yogyakarta academic year 2015/2016 included in the high category. Comparatively, there was a very significant difference of learning results in science using number head together with a model in cooperative learning method and conventional learning method.